Macroeconomic effects of green recovery programmes: Conceptual framing and a review of the empirical literature - Angela Köppl; Margit Schratzenstaller (Austrian Institute of Economic Research (WIFO), 2022)
As governments spend unprecedented sums of public money on pandemic related rescue and recovery measures, while humankind is facing mounting long-term challenges - and above all the climate crisis -, the question whether and to what extent COVID-19 recovery programmes contribute to countries' commitments to a sustainability oriented recovery is gaining increasing urgency. We argue that overcoming the economic and social impacts of the pandemic require deeper structural changes than a return to a more or less business as usual scenario to limit the impacts of climate change. Recovery packages should therefore be designed in such a way as to avoid fossil lock-in effects and take into account that the social and technological actions taken today will unfold their effects in the climate system with a time lag only. An interesting question in this context is the effectiveness of green recovery measures not only with regard to environmental objectives, but also concerning conventional economic indicators, which are traditionally summarised under the heading "multiplier effects". Evaluations of the economic effects of green recovery measures, e.g. those implemented during the global financial crisis, are in short supply. Most of the existing empirical analyses have an ex ante focus, while ex post evaluations are scarce. This paper aims at contributing to this research gap by providing a review of the empirical evidence of the macroeconomic effects of green recovery measures.
Keywords: E62; E65; H12; H23; O44; Q58; 330; green recovery; COVID-19 crisis; multipliers; green multipliers; transformative change